2017
DOI: 10.18240/ijo.2017.11.21
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of uncorrected refractive error in urban, suburban, exurban and rural primary school children in Indonesian population

Abstract: Uncorrected refractive error (URE) is a major health problem among school children. This study was aimed to determine the frequency and patterns of URE across 4 gradients of residential densities (urban, exurban, suburban and rural). This was a cross-sectional study of school children from 3 districts in Yogyakarta and 1 district near Yogyakarta, Indonesia. The information regarding age, sex, school and school grader were recorded. The Snellen's chart was used to measure the visual acuity and to perform the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
9
0
3
Order By: Relevance
“…Another important element for the development of myopia could be attributed to the residential area where children live. A cross-sectional study of school children in Indonesia revealed that the prevalence of uncorrected refractive error was 10.1%, 12.3%, 3.8%, and 1%, respectively among urban, suburban, exurban and rural area [53]. Thus, the higher prevalence among urban and suburban area could be explained with a lack of outdoor activities combined with a more intensive near work due to the higher education in comparison with rural areas.…”
Section: The Role Of the Environmentmentioning
confidence: 99%
“…Another important element for the development of myopia could be attributed to the residential area where children live. A cross-sectional study of school children in Indonesia revealed that the prevalence of uncorrected refractive error was 10.1%, 12.3%, 3.8%, and 1%, respectively among urban, suburban, exurban and rural area [53]. Thus, the higher prevalence among urban and suburban area could be explained with a lack of outdoor activities combined with a more intensive near work due to the higher education in comparison with rural areas.…”
Section: The Role Of the Environmentmentioning
confidence: 99%
“…Therefore, myopia was dominant in other studies, which may be associated with the fact that some studies used an autorefractor without cycloplegic, which overestimates the prevalence of myopia [12], and in others, refraction was performed only in schoolchildren with VA less than 6/6, which may underestimate the prevalence of hyperopia, as it does not always have a low VA.…”
Section: Discussionmentioning
confidence: 99%
“…The objective refraction was static (with a Keeller Professional Streak Retinoscope) without cycloplegic, and then the subjective refraction was performed. Due to the impossibility of using a cycloplegic, the use of an autorefractor was discarded as it could overestimate the prevalence of myopia in students with very active accommodation [12]. To evaluate the ocular structures, anterior and posterior segments, a point flashlight, magnifying loupe and a professional Keeler ophthalmoscope (for direct ophthalmoscopy) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Em estudos internacionais recentes, que realizaram a avaliação em crianças escolares, verificou-se a prevalência de 10,1% na população urbana da Indonésia (15) , 5,8%, na Etiópia (16) , e, em um estudo representativo realizado com crianças multiétnicas em escolas rurais da China (17) , cerca de 7,4% dos escolares apresentaram baixa AV, considerando a medida no melhor olho.…”
Section: Discussionunclassified